Teacher Characteristics and Student Performance: Evidence from Random Teacher-Student Assignments in China - Wei Huang; Teng Li; Yinghao Pan; Jinyang Ren (Institute of Labor Economics (IZA), 2021)
This paper investigates the impacts of teacher characteristics on student performance using a nationally representative and randomly assigned teacher-student sample in China. We find that having a more experienced or female homeroom teacher (HRT) with additional classroom management duties significantly improves students' test scores and cognitive and noncognitive abilities. In contrast, these effects are not observed for subject teachers who are responsible only for teaching. More experienced or female HRTs are also associated with a better classroom environment, more self-motivated students, more parental involvement, and higher parental expectations. These mechanisms explain 10-25 percent of HRT effects on test scores and cognitive ability and 50-60 percent of HRT effects on noncognitive ability. Our findings highlight the importance of teacher management skills in education production.
Keywords: I21; J24; 330; teacher value-added; education production function; student performance